1978
DOI: 10.1051/rnd:19780533
|View full text |Cite
|
Sign up to set email alerts
|

Precocious induction of maturation and ovulation in northern pike (Esox lucius)

Abstract: Summary. The efficiency of partially purified salmon gonadotropin (PPSG) and human chorionic gonadotropin (HCG), administered alone or in association with a progestagen (17a-hydroxy, 20P-dihydroprogesterone : 17!-20! P, or 17a-hydroxyprogesterone : 17a P) was investigated in submature females using the germinal vesicle in non-peripheral position as the criterium for initial oocyte stage. A dose of 0.1 mg PPSG/kg gave satisfactory ovulation (89 p. 100) and fertilization (83 p. 100) rates ; a minimum dose of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 8 publications
1
24
1
Order By: Relevance
“…One spontaneously ovulated female from group 3 had higher fertilization and hatching rates, however, these data were limited and not comparable to other groups. Generally, hatching and fertilization rates found in our study were higher than those reported by other authors (De Montalembert et al, 1978;Billard and Marcel, 1980;Horváth, 1983;Szabó, 2001;2003;2008).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…One spontaneously ovulated female from group 3 had higher fertilization and hatching rates, however, these data were limited and not comparable to other groups. Generally, hatching and fertilization rates found in our study were higher than those reported by other authors (De Montalembert et al, 1978;Billard and Marcel, 1980;Horváth, 1983;Szabó, 2001;2003;2008).…”
Section: Discussioncontrasting
confidence: 56%
“…After a single injection of GnRHa, the duration of GnRHa circulation in blood may be insufficient to stimulate the surge of LH (Crim et al, 1988;Podhorec and Kouril, 2009) that is necessary to complete final oocyte maturation and ovulation in northern pike. Other factors that can influence the progression of gametogenesis are handling stress (De Montalembert et al, 1978) and stage of gonad development (Billard and Marcel, 1980). One solution to this inadequate release profile of GnRHa could be the utilisation of GnRHa delivery systems that stimulates sustained elevation of plasma LH and therefore induces the natural progression of plasma steroid increase that is associated with FOM and ovulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies have shown that 17cu, 20/3-P also induces oocyte maturation in the trout ) carp (Jalabert et al, 1979) and pike (Montalembert et al, 1978). Ovulation only occurred in these studies if the 17a, 2Op-P injections were preceded by a 'priming' injection of hypophysial homogenate.…”
Section: Introductionmentioning
confidence: 99%
“…In lot 3 (2 injections of 17 a-20 p P), there is a small rise in gonadotropin beginning on day 6 and reaching 12 ng/ml on day 15. (Kirshenblat, 1952) ; northern pike (de Montalembert, Jalabert and Bry, 1978).…”
mentioning
confidence: 99%